2021
DOI: 10.1016/j.scitotenv.2021.145721
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on SARS-CoV-2 infectivity in water and wastewater. What do we know?

Abstract: The COVID-19 outbreak circulating the world is far from being controlled, and possible contamination routes are still being studied. There are no confirmed cases yet, but little is known about the infection possibility via contact with sewage or contaminated water as well as with aerosols generated during the pumping and treatment of these aqueous matrices. Therefore, this article presents a literature review on the detection of SARS-CoV-2 in human excreta and its pathways through the sewer system and wastewat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 206 publications
0
88
0
2
Order By: Relevance
“…Multiple activities could bring deer into contact with people, including captive cervid operations, field research, conservation work, wildlife tourism, wildlife rehabilitation, supplemental feeding, and hunting (10). Wildlife contact with contaminated water sources has also been offered as a potential transmission route (11), although transmissibility of SARS-CoV-2 from wastewater has yet to be conclusively demonstrated (26). Transmission from fomites or other infected animal species cannot be discounted.…”
Section: Main Textmentioning
confidence: 99%
“…Multiple activities could bring deer into contact with people, including captive cervid operations, field research, conservation work, wildlife tourism, wildlife rehabilitation, supplemental feeding, and hunting (10). Wildlife contact with contaminated water sources has also been offered as a potential transmission route (11), although transmissibility of SARS-CoV-2 from wastewater has yet to be conclusively demonstrated (26). Transmission from fomites or other infected animal species cannot be discounted.…”
Section: Main Textmentioning
confidence: 99%
“…To date, at least 21 countries have reported the presence of the SARS-CoV-2 RNA in wastewater systems including untreated wastewater, treated wastewater, and sludge ( Table S1 ), but no infectious SARS-CoV-2 has been detected in wastewater and no case of SARS-CoV-2 transmission via contact with sewage or sewage-contaminated water has been reported. 25 , 26 In addition, it has been reported that conventional disinfection of water ensures inactivation of SARS-CoV-2. 27 Several WBE studies have reported the occurrence of local community transmission of SARS-CoV-2 before the first notified clinical SARS-CoV-2 case.…”
Section: Introduction To Wastewater Based Epidemiology Of Sars-cov-2mentioning
confidence: 99%
“…Our analysis was focused on the relationship between SARS-CoV-2 RNA concentrations and 7-day cumulative cases, although a larger time window would also reflect a plausible scenario. SARS-CoV-2 RNA can enter the sewage system through wastewater discharged from households and other establishments frequently inhabited by active carriers, but also from hospitals and isolation facilities ( Giacobbo et al, 2021 ) and may occur in several forms in wastewater which include at least i) infectious protected, ii) non-infectious protected and iii) non-protected forms ( Wurtzer et al, 2021 ). It has been shown that infected persons have been found to excrete the virus for prolonged periods ( Cevik et al, 2021 , Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%